PROBLEMATIKA KEPALA DAERAH SECARA LANGSUNG (DALAM PERSPEKTIF SOSIOLOGIS) - H Djauhari (Faculty of Law, Universitas Jenderal Soedirman, 2011)
Regional Head in a direct election indicates not yielded Regional Head of an ideal, in this case is suspected that some Regional Head who stumble legal cases of corruption. Such things can happen because of the democratic process in elections beginning with the starting pull of interest between the prospective head region with political parties on the one hand, and between candidates for the head area with his constituents on the other side. The implications of these conditions cause the cost of direct elections is quite expensive. With the number of political parties is quite large and there is no consciousness of the voters make choices based on conscience cannot be avoided in the elections always bring money politics (politics of money) / political horse-trading, and will bring leaders think moral hazard. These conditions are still just always happens in local elections democratic party directly. Such a case will be examined from a sociological aspect to bring up three issues, namely: the proliferation of political parties, money politics (money politics) / political horse-trading and the nature of moral hazard. Keywords: direct election problems, sociological perspectives